Evaluation of Allowable Bearing Capacity of Soil by Plate Bearing Test. A Case Study in Al-Diwaniyah City - Abd-Ali, Dr. Mohammed Salih (Basrah Journal for Engineering Sciences, 2013)
The foundation of soil is considered safe when the factor of safety against shear failure is adequate and the settlement of the foundation should be tolerable and does not cause any unacceptable damage for the structure. The ultimate bearing capacity is defined as the maximum pressure which may be applied to the soil without causing neither a shear failure nor large settlement. In this research the bearing capacity of the soil at diesel power plant project in Al-Diwaniyah city by plate bearing test. The soil has been tested in the field in the locations of four foundations for circular tanks of diameter of 17m. The load is applied to the plate in four increments. In each increment; the load stays static for 15 minutes according to ASTM D1194-94 specification. The results showed that the plate settlements of the soil under three tanks were within the permitted settlement. The allowable bearing capacity of soils under these tanks were (117, 137 and 137) kPa respectively. While, the soil under the fourth tank was soft and the plate settled approximately 30 mm immediately after applying the first increment of load. Therefore the soil is considered improper and recommendations are suggested to improve it.